2022
DOI: 10.1002/cncr.34404
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in cervical cancer patients receiving care at National Cancer Institute–designated cancer centers

Abstract: BACKGROUND:Locally advanced cervical cancer (CC) remains lethal in the United States. We investigate the effect of receiving care at an National Cancer Institute-designated cancer center (NCICC) on survival. METHODS: Data for women diagnosed with CC from 2004 to 2016 who received radiation treatment were extracted from the California Cancer Registry (n = 4250). Cox proportional hazards regression models assessed whether (1) receiving care at NCICCs was associated with risk of CC-specific death, (2) this associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…32 The financial, social, and time burdens of the complex multimodal treatments are hardest on disadvantaged populations and introduce many possibilities for substandard care unless needs are addressed directly through navigation or improved care coordination. 33 Delivery of brachytherapy for locally advanced cervical cancer is another important quality metric with documented disparities by race (Black vs. White). [33][34][35][36] Women older than 60 years and those with public insurance or uninsured, care in a nonacademic center, or treatment in the Southern or Western US regions also received less brachytherapy.…”
Section: Disparities In Outcomes and Treatment In Invasive Cervical C...mentioning
confidence: 99%
See 3 more Smart Citations
“…32 The financial, social, and time burdens of the complex multimodal treatments are hardest on disadvantaged populations and introduce many possibilities for substandard care unless needs are addressed directly through navigation or improved care coordination. 33 Delivery of brachytherapy for locally advanced cervical cancer is another important quality metric with documented disparities by race (Black vs. White). [33][34][35][36] Women older than 60 years and those with public insurance or uninsured, care in a nonacademic center, or treatment in the Southern or Western US regions also received less brachytherapy.…”
Section: Disparities In Outcomes and Treatment In Invasive Cervical C...mentioning
confidence: 99%
“…33 Delivery of brachytherapy for locally advanced cervical cancer is another important quality metric with documented disparities by race (Black vs. White). [33][34][35][36] Women older than 60 years and those with public insurance or uninsured, care in a nonacademic center, or treatment in the Southern or Western US regions also received less brachytherapy. 36 Disparities in access to advanced radiation modalities including intensity-modulated radiation therapy lead to long-term toxicities and poorer quality of life.…”
Section: Disparities In Outcomes and Treatment In Invasive Cervical C...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one study found that NCICC had lower adjusted surgical mortality rates than control hospitals for certain surgical procedures 2 . Other studies report superior overall survival for patients with newly‐diagnosed cancers at NCICCs versus non‐designated centers 3,4 . Access to clinical trials may contribute to this survival benefit.…”
Section: Introductionmentioning
confidence: 99%